2011
DOI: 10.1890/es10-00068.1
|View full text |Cite
|
Sign up to set email alerts
|

Dendroecological testing of the pyroclimatic hypothesis in the central Great Basin, Nevada, USA

Abstract: Abstract. In the Great Basin region of western North America, records of past climate and wildfire variability are needed not only for fire use, but also for understanding the mechanisms behind the centurylong expansion of piñon-juniper woodlands. The Mt. Irish area (Lincoln County, south-eastern Nevada) is a remote mountain ecosystem on the hydrographic boundary between the Great Basin and the Colorado River Basin. Non-scarred ponderosa pines (Pinus ponderosa C. Lawson var. scopulorum Engelm.) and singleneedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Irish were consistent with a pre-settlement fire regime characterized by frequent low-severity events (Biondi et al 2011), as trees older than 200 years were found at most plots and gridpoints. Such old-growth individuals are also consistent with a long fire rotation.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Irish were consistent with a pre-settlement fire regime characterized by frequent low-severity events (Biondi et al 2011), as trees older than 200 years were found at most plots and gridpoints. Such old-growth individuals are also consistent with a long fire rotation.…”
Section: Discussionsupporting
confidence: 73%
“…Roughly at the same time, the reduction in wildfire frequency uncovered at both study areas (Biondi et al 2011;Kilpatrick et al, in press) was the main factor that allowed the increased survivorship of pinyon and ponderosa pine. After the early-2000s drought, and despite the greater density they acquired over the past century, the pinyon-juniper populations we studied have not experienced the dramatic mortality observed where P. edulis is present.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations